Influence of social capital on mental health of men who have sex with men: The chain mediating effects of perceived stress and psychological resilience - Xiaoyue Zhang; Ying Zhou; Kaili Zhang (Journal of the Pakistan Medical Association, 2025)
Objective: To probe the influence of social capital on the mental health of men who have sex with men. Method: The study was conducted at the School of Nursing, Xuzhou Medical University, Xizhou, China, from January to December 2023, and comprised men who have sex with men. Data was collected online using the Social Capital Questionnaire, Perceived Stress Scale, Connor-Davidson Resilience Scale and Self-Rating Mental Health Scale. Data was analysed using SPSS 24. Results: Of the 624 questionnaires distributed, 546(87.5%) men returned them fully filled. The mean age of the respondent was 27.77±7.77 years. Social capital, perceived stress, psychological resilience and mental health were significantly correlated with each other (p<0.001). Perceived stress and resilience possessed a significant mediating effect in social capital along with mental health, with effect sizes being 60.32% and 17.41%, respectively. Perceived stress-psychological resilience harboured a significant chain mediating effect in social capital along with mental health, with the effect size being 6.48%. Conclusion: Social capital could affect the mental health of men who have sex with men not only through the independent mediating influence of perceived stress and psychological resilience, but also through the chain mediating influence of perceived stress-psychological resilience. Keywords: Men who have sex with men, Social capital, Mental health, Perceived stress, Psychological resilience.